Uncovering the unique characteristics of the mandible to improve clinical approaches to mandibular regeneration - Soares, Ana Prates; Fischer, Heilwig; Aydin, Sabrin; Steffen, Claudius; Schmidt-Bleek, Katharina; Rendenbach, Carsten (Frontiers in Physiology, 2023)
The mandible (lower jaw) bone is aesthetically responsible for shaping the lower face, physiologically in charge of the masticatory movements, and phonetically accountable for the articulation of different phonemes. Thus, pathologies that result in great damage to the mandible severely impact the lives of patients. Mandibular reconstruction techniques are mainly based on the use of flaps, most notably free vascularized fibula flaps. However, the mandible is a craniofacial bone with unique characteristics. Its morphogenesis, morphology, physiology, biomechanics, genetic profile, and osteoimmune environment are different from any other non-craniofacial bone. This fact is especially important to consider during mandibular reconstruction, as all these differences result in unique clinical traits of the mandible that can impact the results of jaw reconstructions. Furthermore, overall changes in the mandible and the flap post-reconstruction may be dissimilar, and the replacement process of the bone graft tissue during healing can take years, which in some cases can result in postsurgical complications. Therefore, the present review highlights the uniqueness of the jaw and how this factor can influence the outcome of its reconstruction while using an exemplary clinical case of pseudoarthrosis in a free vascularized fibula flap.